2021
DOI: 10.3390/jcm10081713
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Etiology and Prognosis in Men and Women with Acute Heart Failure

Abstract: Coronary heart disease is common in heart failure (HF). Our aim was to determine the impact of ischemic etiology on prognosis among men and women with HF. This study is a prospective national multicenter registry. The primary endpoint was 12-month mortality. Patients with HF and ischemic heart disease were stratified according to sex. A total of 1830 patients were enrolled of which 756 (41.3%) were women. Ischemic etiology was more common in men (446 (41.6%)) than in women (167 (22.2%)). Among patients with is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The non-ischaemic aetiology correlated with a higher risk of rehospitalisation and death, as observed in a comparative analysis between patients with AHF of ischaemic and non-ischaemic aetiology from the "OP-AHF" registry, a single-centre study enrolling 122 patients; similarly, the same was also observed in a subanalysis of the Spanish Network for the Study of Heart Failure II registry (REDINSCOR II), a multicentre study with a larger population sample (1830 patients with AHF) [28,29]. An elevated creatinine level and prior HF hospitalisation were associated with a poor outcome as observed by Ruigómez et al [30].…”
Section: Discussionmentioning
confidence: 55%
“…The non-ischaemic aetiology correlated with a higher risk of rehospitalisation and death, as observed in a comparative analysis between patients with AHF of ischaemic and non-ischaemic aetiology from the "OP-AHF" registry, a single-centre study enrolling 122 patients; similarly, the same was also observed in a subanalysis of the Spanish Network for the Study of Heart Failure II registry (REDINSCOR II), a multicentre study with a larger population sample (1830 patients with AHF) [28,29]. An elevated creatinine level and prior HF hospitalisation were associated with a poor outcome as observed by Ruigómez et al [30].…”
Section: Discussionmentioning
confidence: 55%
“…There are several sex differences in patients with HF previously reported, as traditional risk factors, pathophysiology and response to treatment differs between men and women ( 10 , 11 , 14 , 15 ). In a large multicentre study, including >80,000 hospitalized patients, Hsich et al described, more than a decade ago, that women with HF were usually older than men, more likely to have hypertension and depression and less likely to have coronary or peripheral artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…The last decades witnessed an improvement in CAD-treatment modalities, with reduced its associated mortality and increasing survival after myocardial infarction [MI]. However, the incidence of CAD continued to increase, as a result of the increased percentages of aging population [2] .…”
Section: Introductionmentioning
confidence: 99%